Complex associations between cross‐kingdom microbial endophytes and host genotype in ash dieback disease dynamics. (28th October 2019) - Griffiths, Sarah M.; Galambao, Marciana; Rowntree, Jennifer; Goodhead, Ian; Hall, Jeanette; O'Brien, David; Atkinson, Nick; Antwis, Rachael E.
Abstract: Tree pathogens are a major threat to forest ecosystems. Conservation management strategies can exploit natural mechanisms of resistance, such as tree genotype and host‐associated microbial communities. However, fungal and bacterial communities are rarely looked at in the same framework, particularly in conjunction with host genotype. Here, we explore these relationships and their influence on ash dieback disease, caused by the pathogen Hymenoscyphus fraxineus, in European common ash trees. We collected leaves from UK ash trees and used microsatellite markers to genotype trees, quantitative PCR to quantify H. fraxineus infection load and ITS and 16S rRNA amplicon sequencing to identify fungal and bacterial communities, respectively. There was a significant association between H. fraxineus infection intensity and ash leaf fungal and bacterial community composition. Higher infection levels were positively correlated with fungal community alpha‐diversity, and a number of fungal and bacterial genera were significantly associated with infection presence and intensity. Under higher infection loads, leaf microbial networks were characterized by stronger associations between fewer members than those associated with lower infection levels. Together these results suggest that H. fraxineus disrupts stable endophyte communities after a particular infection threshold is reached, and may enable proliferation of opportunistic microbes. We identified three microbial genera associated with an absence of infection, potentially indicating an antagonistic relationship with H. fraxineus that could be utilized in the development of anti‐pathogen treatments. Host genotype did not directly affect infection, but did significantly affect leaf fungal community composition. Thus, host genotype could have the potential to indirectly affect disease susceptibility through genotype × microbiome interactions, and should be considered when selectively breeding trees. Synthesis . We show that the diversity, composition and network structure of ash leaf microbial communities are associated with the severity of infection from ash dieback disease, with evidence of disease‐induced dysbiosis. We also show that host genotype influences leaf fungal community composition, but does not directly influence tree infection. These findings help to elucidate relationships between host genetics, the microbiome and a tree pathogen, highlighting potential resistance mechanisms and possible co‐infection concerns that could inform ash tree management. Abstract : We show that the diversity, composition and network structure of ash leaf microbial communities are associated with the severity of infection from ash dieback disease, with evidence of disease‐induced dysbiosis. We also show that host genotype influences leaf fungal community composition, but does not directly influence tree infection. These findings help to elucidate relationships between host genetics, the microbiome and a tree pathogen, highlighting potential resistance mechanisms and possible co‐infection concerns that could inform ash tree management.